A Pilot Study of Pro-Urokinase in the Treatment of Deep Vein Thrombosis - Mola, Marco; Mannucci, Pier Mannuccio; Pini, Marlo; Prandoni, Paolo; Gurewich, Victor (Thrombosis and Haemostasis, 1994)
Safety and efficacy of the thrombolytic agent pro-urokinase (pro-UK) in the treatment of deep vein thrombosis of the lower limbs (DVT) have been investigated in an open, uncontrolled, pilot study. Fifteen patients were infused with 800.000 IU (5 mg)/h of pro-UK over 24 h (120 mg), together with unfractionated heparin adjusted to maintain the activated partial thromboplastin time between 1.5 and 2.5 times the basal value. Efficacy was assessed comparing venographic changes in the 11 evaluable limbs before and after pro-UK infusion. The Marder score decreased from a median pre-thrombolysis value of 28 (range 4-40) to 16 (3-38) (p <0.05). One major hemorrhagic event (retroperitoneal bleeding 4 days after the end of the pro-UK infusion) occurred. Fibrinogen, alpha2-antiplasmin and plasminogen significantly decreased from baseline values after 12 and 24 h, fibrin(ogen) degradation products significantly increased. Changes in hemostasis parameters were unrelated to thrombolytic efficacy. The results of this pilot study indicate that pro-UK is thrombolytic in DVT and that it can be administered simultaneously with conventional heparin treatment.